Work-Life-Balance: Gedanken des Perspektivforums Junge Chirurgie der Deutschen Gesellschaft für Chirurgie = Work-life balance : thoughts of the Young Surgeon representatives of the German Surgical Society - Braun, Benedikt Johannes; Anetsberger, Stephanie (Der Chirurg, 2018)
Work-life balance is a commonly used term that appears in different contexts and has a different meaning for many colleagues. Unfortunately, however, it is often used as a negative, simplified term to describe the assumed attitude of young surgeons towards work and a medical career, even though this is not universally applicable. As the representatives for Young Surgeons of the German Society of Surgery the aim of this article is to present our thoughts on the issue and associated problems and provide a differentiated outline for discussion.